Sick Role Condition: Correlation of Knowledge Level on Covid-19 Transmission and Increasing Healthy Living Behaviours Practice in the Family - Kabelen, Marista Christina Shally; Jahja, Rusfadia Saktiyanti (Komunitas, 2022)
This study reviews aspect of the Covid-19 pandemic that is currently engulfing Indonesia and the application of a clean and healthy lifestyle which is believed to be able to suppress the spread of the Covid-19 virus. This study aims to determine the level of public knowledge regarding the spread of Covid-19, the level of change in the application of the Healthy Living Behaviors, whether there is a correlation between the two variables, and how the relationship with Talcott Parsons' sick role theory on existing relationships and changes.  There have been several studies related to the relationship between the level of knowledge related to covid and behavior but very limited study that also analyzed the efforts to maintain the changes that have been made The research uses a quantitative method approach to test the existing hypotheses. The determination of the data sample was carried out by purposive sampling with the data population of Indonesian citizens resided in Jakarta-Bogor-Depok-Tangerang-Bekasi city (Jabodetabek), with an education level of one family member at least S-1. The results of the study concluded that there was a significant positive relationship with the coefficient value in a sufficient range of relationships between the variables. The level of public knowledge about the spread of Covid-19 is at a fairly high level, (4.03 out of 5). The level of change in the implementation of PHBS is low-medium (2.28 out of 5). The community is depicted as consciously choosing to keep their distance and withdraw from social interaction as an effort to prevent Covid-19, meaning they choose to be in a sick role condition even though they are physically fine.